PERAN CITRA MEREK DALAM MENARIK MINAT KONSUMEN PADA PRODUK LOKAL: Menelaah Peran Citra Merek dalam Membentuk Niat Beli Konsumen terhadap Produk Lokal: Tinjauan Pustaka - Aida Aprilia; Moh. Mukhsin (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2026)
This study aims to conceptually examine the role of brand image in shaping consumer purchase intention toward local products, as well as to identify its supporting factors. The method used is strictly library research with a descriptive-analytical approach, synthesizing various previous literature from published academic journals. The results of the literature synthesis indicate that purchase intention does not form in a vacuum but is triggered by functional advantages (product innovation, price perception, and digital promotion). Furthermore, this study confirms the theoretical position of brand image as the main mediator variable or "psychological bridge". Rather than empirically proving statistical correlation, this study finds that across the literature, brand image consistently acts as a mitigator of perceived risk, transforming consumer doubt into actual interest. The implication is that local business actors are required not only to focus on physical quality but also to build brand reputation in parallel. This study recommends further empirical testing to quantitatively measure the scale of this mediation effect in the field